Consumo de vegetales a partir de evidencias microbotánicas dentro de los sedimentos de cerámica de La Fortaleza, Kuélap - Mayanga Cornejo, Rosa María (2022)
The present investigation involves a sample of ceramic fragments that present microbotanical evidence within the ceramic sediments that come from the La Fortaleza site, Kuelap corresponding to the 2010 excavation season. The objective of the investigation has been to determine the food consumption vegetables through the microbotanical study identifying the identity of the starch grains. The result has revealed the presence of starch grains of Zea mays "Corn" and Manihot esculenta “Cassava” whose characteristics and measurements have been recorded, as well as their microphotographic record. At the same time, a ceramic review was carried out based on the description and comparison with ceramic samples from ancient excavations made on the site to compare them with the samples studied. Therefore, it is proposed that these vegetables were stored in urpos, pitchers, pots, plates and/or keros, which demonstrate their importance for the nutrition of the inhabitants of the Chachapoyas society, who probably consumed them in their rituals and/or ceremonies carried out. In La Fortaleza, Kuelap. Finally, it is stated that this research was carried out in the Archaeobiology Laboratory of the Professional School of Archeology of the Faculty of Social Sciences and in the Laboratory of the Andean Archaeological and Palaeoecological Research Center ARQUEOBIOS.